Etiquette in the Family and the Role of Parents - Ergasheva Durdona Safarali kizi (Zien Journals, 2023)
This research paper delves into the realm of family etiquette and the pivotal role parents play in its cultivation. Family etiquette encompasses a set of social norms and behaviors that guide interactions within the family unit, promoting respectful communication, empathy, and conflict resolution. Through a systematic literature review and qualitative interviews with parents, this study explores the significance of family etiquette, the influence of parents, challenges faced by parents, and effective strategies employed in fostering positive family dynamics. The findings underscore the importance of family etiquette in shaping harmonious relationships and children's social development. Parents emerge as primary influencers, with their modeling of proper etiquette behaviors and consistent guidance playing a critical role. However, challenges such as time constraints and generational differences can hinder parents' efforts. Practical strategies, including consistent routines, open communication, clear expectations, and positive reinforcement, are identified as effective approaches. This research contributes to the understanding of family dynamics and provides insights for parents, educators, and policymakers to nurture strong, respectful, and connected families
Keywords: family etiquette; social; parents